Sistem Pemantauan Parameter Kelistrikan berbasis Komunikasi LoRaWAN dengan Platform Antares - Fredre Nico Panggabean; Sigit Pramono; Anjar Taufik Hidayat (Journal of Electronic and Electrical Power Applications, 2023)
Electrical power is an important parameter to determine how much electrical energy is consumed or produced. Some systems that consume or generate electricity are located in remote or difficult-to-reach locations, for example monitoring volcanoes or micro-hydro power plants at the mountains. Therefore, we need a tool to monitor the electric power from afar. In this research a tool has been designed that can monitor electrical energy with the PZEM004T-10A sensor in real time using the LoRaWAN network on the Antares platform. From the results of system testing, it can be concluded that the designed system can run well according to its function. The results of the average percentage error reading of the PZEM004T sensor against the power meter measuring instrument show a very good value where the average error obtained in the voltage parameter is 0.45%, while the error value obtained for the current parameter is 0.22%, power is 1.44% and power factor of 0.15%. The performance of the Quality of Service delay value on the network according to the standard criteria issued by TIPHON, the delay value produced by SF7 and SF10 is categorized as a bad delay. Then the delay on SF9 and SF12 is included in the good category, and the delay produced by SF8 and SF11 is categorized as a very good delay. Meanwhile, the packet loss value is included in the very good criteria for SF8-SF12 and good for SF 7.